Trending theory of the public sphere. Issue 1 (2nd January 2017) - Jacobson, Thomas
ABSTRACT: Most references to public sphere theory in the literature of media and communication research today focus on Jürgen Habermas's early book The Structural Transformation of the Public Sphere . Since this book's publication the theory of the public sphere has advanced in a number of ways. Early criticisms have in many ways been accommodated. The public sphere has been elaborated within theories of deliberative democracy and social evolution. Most recently, Habermas and other theorists of the public sphere have turned towards the challenges of transnational power and the growing public prominence of religious thought and belief. Recent books on the public sphere review and advance this more recent thinking. This essay reviews three of these books.